German aid allocation and partner country selection: development-orientation, self-interests and path dependency - Jörg Faust; Sebastian Ziaja (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
This paper examines official country selection and resource allocation of German aid after the end of the Cold War and embeds the analysis into the broader debate about German foreign policy. Based on new data, we take into account several peculiarities of the German aid system. Overall, we find that neediness and democracy levels of recipients have been guiding principles in both, country selection and resource allocation. Nevertheless, geo-strategic considerations and the avoidance of conflict-affected countries also impacted on country selection but less on resource allocation. Moreover, non-linear estimation techniques identify a relatively high threshold of income levels below which the poverty orientation disappears; a finding that refines previous studies identifying a middle-income-country bias of German aid allocation. Finally, official selection decisions to concentrate aid on a reduced number of countries did not have the intended concentration effect. This strong path dependency and development-orientation is compatible with research that sees German foreign policy after re-unification as being subject only to very gradual changes and led by the role model of a Civilian power.
Keywords: 330